2002
DOI: 10.1177/107424840200700301
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Following Investigation of Rhythm Management: AFFIRM Trial Outcomes. What Might Be Their Implications for Arrhythmia Control?

Abstract: During the last decade or so, major changes have been made in the approaches to the control of supraventricular as well as ventricular tachyarrhythmias. A few landmarks need emphasis. A precise understanding of the mechanisms of the origin of cardiac arrhythmias led to the development of electrode catheter ablative techniques; these developments have resulted in an extraordinary high degree of success in curing a very large proportion of patients with re-entrant supraventricular arrhythmias. This striking degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Previous reports on QOL in AF Versus SR. Across most QOL domains of the SF-36, patients with persistent or intermittent AF consistently experience a greatly worse QOL compared with that of healthy controls (7)(8)(9)14,20). However, the clinical evidence that conversion and maintenance of SR in patients with AF may predictably result in improvement of QOL continues to be the subject of vigorous debate (21,22). The debate may have stemmed largely from the results of the AFFIRM trial (4).…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports on QOL in AF Versus SR. Across most QOL domains of the SF-36, patients with persistent or intermittent AF consistently experience a greatly worse QOL compared with that of healthy controls (7)(8)(9)14,20). However, the clinical evidence that conversion and maintenance of SR in patients with AF may predictably result in improvement of QOL continues to be the subject of vigorous debate (21,22). The debate may have stemmed largely from the results of the AFFIRM trial (4).…”
Section: Discussionmentioning
confidence: 98%
“…On multiple logistic regression, the only two variables that correlated with successful maintenance of sinus rhythm at 12 months were drug treatment with amiodarone (OR = 2.5; 95% CI, 0.59 to 10.8; P = .013) and QOL score at baseline of 3 or greater (OR = 0.41; 95% CI, 0.18 to 0.92; P = .035). Relatively small clinical studies have indicated that in atrial fibrillation from nonvalvular disease, exercise capacity is increased on the restoration of sinus rhythm (19-21), but this has recently been challenged on the basis of the outcome data from larger controlled clinical trials (12,13), most notably by the AFFIRM trial (13). On the other hand, a recent double-blind placebo-controlled trial in persistent atrial fibrillation has shown that restoration and maintenance of sinus rhythm is associated with an increase in exercise capacity and QOL (22).…”
Section: Rhythm Control-amiodarone Versus Placebomentioning
confidence: 99%
“…restoration and maintenance of sinus rhythm in patients with atrial fibrillation (11). Symptomatic improvement in the sinus rhythm group has been suggested by the Pharmacological Intervention in Atrial Fibrillation (PIAF) (12) trial, but mortality benefit in the large multicenter Atrial Fibrillation Follow Up Investigation of Rhythm Management (AFFIRM) study (13) has not been confirmed.…”
mentioning
confidence: 99%
“…There was no significant impact on mortality but sustained sinus rhythm was associated with significantly improved quality of life as well as exercise performance on standardized treadmill test. Thus, in contrast to the findings in the AFFIRM trial, these overall data are clearly in favor of restoration and maintenance of sinus rhythm in patients with AF in which there is scope for improving exercise capacity, symptoms, and quality of life [32]. A similar conclusions has also been reached in clinical trials that were not as rigorously planned and monitored [ …”
Section: Lessons From Recent Clinical Trials In Afmentioning
confidence: 47%